Radiation leakage dose from Elekta electron collimation system - Pitcher, Garrett M. (J Appl Clin Med Phys, 2016)
This study provided baseline data required for a greater project, whose objective was to design a new Elekta electron collimation system having significantly lighter electron applicators with equally low out‐of field leakage dose. Specifically, off‐axis dose profiles for the electron collimation system of our uniquely configured Elekta Infinity accelerator with the MLCi2 treatment head were measured and calculated for two primary purposes: 1) to evaluate and document the out‐of‐field leakage dose in the patient plane and 2) to validate the dose distributions calculated using a BEAMnrc Monte Carlo (MC) model for out‐of‐field dose profiles. Off‐axis dose profiles were measured in a water phantom at 100 cm SSD for 1 and 2 cm depths along the in‐plane, cross‐plane, and both diagonal axes using a cylindrical ionization chamber with the [Formula: see text] and [Formula: see text] applicators and 7, 13, and 20 MeV beams. Dose distributions were calculated using a previously developed BEAMnrc MC model of the Elekta Infinity accelerator for the same beam energies and applicator sizes and compared with measurements. Measured results showed that the in‐field beam flatness met our acceptance criteria ([Formula: see text] on major and [Formula: see text] on diagonal axes) and that out‐of‐field mean and maximum percent leakage doses in the patient plane met acceptance criteria as specified by the International Electrotechnical Commission (IEC). Cross‐plane out‐of‐field dose profiles showed greater leakage dose than in‐plane profiles, attributed to the curved edges of the upper X‐ray jaws and multileaf collimator. Mean leakage doses increased with beam energy, being 0.93% and 0.85% of maximum central axis dose for the [Formula: see text] and [Formula: see text] applicators, respectively, at 20 MeV. MC calculations predicted the measured dose to within 0.1% in most profiles outside the radiation field; however, excluding modeling of nontrimmer applicator components led to calculations exceeding measured data by as much as 0.2% for some regions along the in‐plane axis. Using EGSnrc LATCH bit filtering to separately calculate out‐of‐field leakage dose components (photon dose, primary electron dose, and electron dose arising from interactions in various collimating components), MC calculations revealed that the primary electron dose in the out‐of‐field leakage region was small and decreased as beam energy increased. Also, both the photon dose component and electron dose component resulting from collimator scatter dominated the leakage dose, increasing with increasing beam energy. We concluded that our custom Elekta Infinity with the MLCi2 treatment head met IEC leakage dose criteria in the patient plane. Also, accuracy of our MC model should be sufficient for our use in the design of a new, improved electron collimation system. PACS number(s): 87.56.nk, 87.10.Rt, 87.56.J